2014
DOI: 10.3390/ijms15046265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Method for Nitrotyrosine Site Identification and Relative Quantitation Using a Stable Isotope-Labeled Nitrated Spike-In Standard and High Resolution Fourier Transform MS and MS/MS Analysis

Abstract: The overproduction of reactive oxygen and nitrogen species (ROS and RNS) can have deleterious effects in the cell, including structural and possible activity-altering modifications to proteins. Peroxynitrite is one such RNS that can result in a specific protein modification, nitration of tyrosine residues to form nitrotyrosine, and to date, the identification of nitrotyrosine sites in proteins continues to be a major analytical challenge. We have developed a method by which 15N-labeled nitrotyrosine groups are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The abundance of protein or Tyr residues cannot predict whether they will be the target of PTN. Furthermore, not all Tyr residues in a protein are available for nitration, which may depend on their accessibility to the solvent [10,15]. For instance, although the human serum albumin (HSA), a protein most abundantly found in plasma, contains 18 Tyr residues, an in vitro study showed that only two of its Tyr residues are predominantly susceptible to nitration [14,16].…”
Section: Nitrotyrosine In Physiological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of protein or Tyr residues cannot predict whether they will be the target of PTN. Furthermore, not all Tyr residues in a protein are available for nitration, which may depend on their accessibility to the solvent [10,15]. For instance, although the human serum albumin (HSA), a protein most abundantly found in plasma, contains 18 Tyr residues, an in vitro study showed that only two of its Tyr residues are predominantly susceptible to nitration [14,16].…”
Section: Nitrotyrosine In Physiological Conditionsmentioning
confidence: 99%
“…Several physiological and pathological conditions have been associated with increased nitration of proteins [15,21]. Table 1 shows the 3-NT concentration range usually found in both healthy and pathological states, as determined by different methods (discussed in detail in the following sections) and biological samples.…”
Section: Association Between 3-nitrotyrosine and Diseasementioning
confidence: 99%
“…[53] Moreover, efforts are also made for developing various methods to identify nitration protein and nitrotyrosine site. [54,55] With the development of novel techniques for special assessment of not only ONOO − but also nitration protein and nitrotyrosine sites, we will be able to better understand the oxidation and redox mechanisms in both physiological and pathological conditions. The progress offers new opportunities and platforms for drug discovery targeting peroxynitrite and other free radicals for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate identification of nitrotyrosine sites is an essential foundation for revealing the mechanism and function of nitroproteins [ 13 , 14 ]. To identify nitrotyrosine sites, various large-scale proteomic studies are widely adopted in numerous organisms, including Bacillus licheniformis , Bacillus subtilis , Bos taurus , Bungarus multicinctus , Capsella bursa-pastoris , Carica papaya , Cricetulus migratorius , Enterobacteria phage fd , Escherichia phage lambda , Enterobacteria phage T4 , Enterococcus faecalis , Escherichia coli , Fusarium oxysporum , Halobacterium salinarum , Hirudo medicinalis , Homo sapiens , Mus musculus , Naja atra , Naja melanoleuca , Neurospora crassa , Ophiophagus hannah , Oryctolagus cuniculus , Ovis aries , Finegoldia magna , Phascolopsis gouldii , Physeter catodon , Pseudomonas putida , Rattus norvegicus , Rhodococcus rhodochrous , Saccharomyces cerevisiae , Schizophyllum commune , Staphylococcus aureus , Streptomyces albogriseolus , Struthio camelus , Sus scrofa , Thermus thermophilus , Tobacco mosaic virus , and Protobothrops flavoviridis [ 1 , 7 , 8 , 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To identify nitrotyrosine sites, various large-scale proteomic studies are widely adopted in numerous organisms, including Bacillus licheniformis , Bacillus subtilis , Bos taurus , Bungarus multicinctus , Capsella bursa-pastoris , Carica papaya , Cricetulus migratorius , Enterobacteria phage fd , Escherichia phage lambda , Enterobacteria phage T4 , Enterococcus faecalis , Escherichia coli , Fusarium oxysporum , Halobacterium salinarum , Hirudo medicinalis , Homo sapiens , Mus musculus , Naja atra , Naja melanoleuca , Neurospora crassa , Ophiophagus hannah , Oryctolagus cuniculus , Ovis aries , Finegoldia magna , Phascolopsis gouldii , Physeter catodon , Pseudomonas putida , Rattus norvegicus , Rhodococcus rhodochrous , Saccharomyces cerevisiae , Schizophyllum commune , Staphylococcus aureus , Streptomyces albogriseolus , Struthio camelus , Sus scrofa , Thermus thermophilus , Tobacco mosaic virus , and Protobothrops flavoviridis [ 1 , 7 , 8 , 10 , 14 , 15 ]. Despite the increasing number of experimentally identified nitrotyrosine sites, the mechanism of site-specific nitration modifications on tyrosine still remains largely unknown, possibly because of the constraints of measurement technologies [ 3 , 12 , 13 ]. On the other hand, experimental verification of nitrotyrosine sites is time-consuming, labor-intensive, and sometimes biased toward the abundant proteins.…”
Section: Introductionmentioning
confidence: 99%